Trust in science: a critical review of the complex interactions between credibility and trust associated with conservation science - Horton, Cristi Choat; Lane, Rachel; Peterson, Tarla R. (Frontiers in Communication, 2025)
The credibility enjoyed by natural science and scientists during most of the 20th Century has been challenged in the 21st Century. Philosophers of science have noted waning trust in science as an appropriate foundation for sociopolitical decisions. Conservation science literature explores credibility-trust relationships to understand how these interactions contribute to or detract from scientific legitimacy. We conducted a content analysis of professional literature to determine how credibility was framed in conservation science as it relates to trust. We discovered that the literature has limited recognition of credibility’s multidimensionality and the emergent nature of credibility and trust. Both were framed as static entities, thereby restricting understanding that these constructs are co-created within each situation to create a set of expectations that, when met, increases message effectiveness and enhances trust. Scientists’ credibility is an essential precursor (i.e., antecedent) to establishing trust. We suggest that conservation scientists could more effectively enhance their credibility through the recognition that it develops along the dimensions of expertise, goodwill, and honesty and that trust involves mutual vulnerability. Armed with a more nuanced understanding of credibility’s multidimensionality and an increased understanding that credibility and trust interactions are sociopolitical processes, conservation scientists are enabled to deconstruct existing terminologies and reframe them in ways that better meet and fulfill stakeholders’ expectations to enhance trust and mitigate its erosion.